Amianto: un riesgo olvidado de los profesionales dentales. - Anaya-Aguilar, Carmen; Anaya-Aguilar, Rosa María; Rosel, Eva; Bravo, Manuel (Círculo de Odontólogos y Estomatólogos, 2023)
Asbestos is the name of a mineral that occurs in the form of small, flexible fibers that has traditionally been used as an insulator against heat and fire. The detached fibers that reach the lungs through breathing can cause diseases such as lung cancer, mesothelioma and other pathologies related to its use such as asbestosis or a type of pneumoconiosis produced by this inhalation that causes pulmonary fibrosis. Dentistry has not been left out of this massive use of asbestos, thus, the review of the literature shows a potential exposure to asbestos for professionals in the dental sector. According to the International Commission on Occupational Medicine (CIMIT), asbestos claims approximately 88,000 lives in Europe each year, accounting for 55-85% of lung cancers at work. and as far as the authors know, there are no prevention plans in the dental profession in relation to the carcinogenic agent of asbestos, so in view of the above, we set the objective of this study to remind dental professionals of the risk of exposure to asbestos. to which they have been exposed in their professional work by analyzing the opinions of a group of experts with experience in the sector.
https://rebiunoda.pro.baratznet.cloud:28443/OpacDiscovery/public/catalog/detail/b2FpOmNlbGVicmF0aW9uOmVzLmJhcmF0ei5yZW4vMjA3OTEzMzE Título: Labor dental clínica avances clínicos en odontoestomatología Editorial: [Martorell] Ed. Especializadas Europeas SL [2018]- Descripción física: recurs en línia Periodicidad actual: Quadrimestral Variantes del título: Revista labor dental clínica Nota general: Inclou taules A partir del 2021 bilingüe castellà-portuguès Bibliografía: Bibliografia Formato físico adicional: Posteriorment accés gratuït previ registre a la web Lengua: Extractes en castellà i anglès ISSN: 2696-5100 1888-4040 Materia: Odontología- Revistes. Enlace a título anterior: Labor dental clínica 1888-4040
Sólo para usuarios (profesionales) registrados; sin política de autoarchivo.
Keywords: Intoxicación por asbesto; Dentistas - Salud; Asbestos; Dental professional; Safety and health